Job Sustainability in the Expanded Public Works Programme for Gauteng Province - Zondi, Jabulile (My University, 2011)
Determined to reduce unemployment and poverty, and to stimulate economic growth, workplace productivity and social development, the South African government introduced a wide range of socio-economic reforms after 1994. Of these reforms, training and skills development in particular took a centre stage in the government‟s national agenda, as both public and private organisations experienced a deepening skills crisis. The skills crisis not only constrained South Africa‟s economic competitiveness, but also cost the country dearly with regard to job sustainability, reduced productivity and social development. In the public sector, in particular, government sought to accelerate job creation through the Expanded Public Works Programme (EPWP), with training as a key component. The purpose of this research, which relied on the case study method, was to explore the implementation of skills programmes in the Expanded Public Works Programme in the Gauteng province from 2006 to 2009 in order to determine the sustainability of the jobs created through these initiatives. The findings of the research revealed that the outcomes from these training initiatives were short-lived, fragmented and thus not sustainable. On the basis on these findings, it was then proposed that the current skills development framework in the EPWP be reviewed and realigned so that it focuses more on national human resource development; which is critical in ensuring job sustainability, workforce flexibility and economic productivity
MM - P&DM
Keywords: Expanded Public Works Programme, Gauteng; Job sustainability